Testing an implementation strategy bundle on adoption and sustainability of evidence to optimize physical function in community-dwelling disabled and older adults in a Medicaid waiver: a multi-site pragmatic hybrid type III protocol - Sandra L. Spoelstra; Monica Schueller; Alla Sikorskii (Implementation Science, 2019)
Abstract Background In partnership with a state Medicaid home and community-based waiver program, this study tests implementation strategies for adoption and sustainability of an evidence-based intervention to support disabled and older adults who have difficulty with physical function and daily living tasks. A multi-level implementation strategy bundle will be directed at relationship, coalition, and team building; readiness to implement, leadership, and clinician attitude toward evidence assessments; intervention and facilitation training; interdisciplinary coordination; facilitation; and audit and feedback to support practice change. Methods Knowledge-to-Action model underpins this 2-arm, 3-year pragmatic mixed method randomized hybrid type III trial in 18 waiver program sites in Michigan. Data will be collected on sites, 775 clinicians (registered nurses, occupational therapists, social workers), and 15,000 disabled and older adults. Consolidated Framework for Implementation Research guides examination of site, clinician, and beneficiary characteristics; clinician attitude and self-efficacy; leadership and readiness to implement; and intervention impact on beneficiary outcomes. Sites will be randomized to either usual waiver care with internal facilitation of the bundle of implementation strategies or usual waiver care with both internal and external facilitation of the bundle. Primary outcomes are site-level adoption and sustainability over 12 months, and intervention effects on these outcomes are hypothesized to be mediated by clinicians’ attitude and self-efficacy. At the beneficiary level, by addressing the individual’s capabilities and home environment, the intervention is hypothesized to improve secondary outcomes of activities of daily living, pain, depression, falls, emergency department visits, and hospitalizations. Baseline site readiness and leadership and stages of implementation at 6 months will be explored as potential moderators. Linear mixed effects models will be used to test intervention effects on primary outcomes, with bias-correcting analytic strategy in mediation analyses. Generalized linear mixed effects modeling will be employed for the analysis of intervention effects on secondary outcomes. Discussion Synthesizing findings within and across the sites, we will specify how leadership, readiness for change, and level of facilitation enhance capacity for adoption and sustainability of an evidence-based intervention in an under-resourced Medicaid setting that cares for disabled and older adults. Trial registration ClinitalTrials.gov, NCT03634033. Registered 16 August 2018.